Cultural pedagogy and it’s development on the threshold of 3rd decade of 21st century - Janusz Gajda (Studia z Teorii Wychowania)
This paper - as stated in the title - covers theory, research and practice of cultural pedagogy in Poland, especially at the beginning of 3rd decade of 21st century. It consists of 2 parts concerning the following issues:History until the end of 20th centuryTradition, origin, subject and philosophical assumptions Cultural pedagogy in the interwar period in PolandCultural pedagogy as a humanistic pedagogy after 2nd World War2. Return of cultural pedagogy after 1995 and it’s further developmentCultural pedagogy, it’s humanistic-anthropological characterImportant publications and academic centers which popularize cultural pedagogySummaryConnecting theory and practice is a requirement for effective education and development of humanistic-anthropological cultural pedagogy which is open to „real world” and „symbolic world”. The last statement, justified in the Summary, is the main thesis of this paper.